Construction of CuS/ZnS heterostructures with enhanced photocatalytic activities on dye degradation and Cr (VI) reduction. Issue 1 (10th September 2022) - Jiao, Yongxin; Wang, Shu; Yin, Jianan; Li, Xin; Liu, Yupu
Abstract: The CuS/ZnS nanocomposites with particle morphology were prepared by ion exchange method. The systemically characterizations were used to study the phase structure, morphology, heterojunction, surface chemical components and optical properties. Furthermore, photocatalytic properties were researched by using 20 mg/L methylene blue and 40 mg/L of potassium dichromate solution as photocatalytic ox-red indicators, respectively. The results showed that the ZnS/CuS composites degraded 86.1% methylene blue solution within 50 min, which was 2.2 times higher than that of bare CuS nanoparticles. Significantly, the degradation rate of Cr (VI) reached 96.6% only within 8 min, which was greatly higher than that of each single component. Therefore, selecting appropriate semiconductors to construct type I-type hetero-structured composite materials could also take into account the three aspects' efficiency of photo-quantum absorption, photogenerated charge transfer separation and surface chemical reaction for modifying the photocatalytic property, which provided a reliable experimental basis for the design and development of efficient solar energy conversion materials.